DAMPAK KRISIS EKONOMI YUNANI TERHADAP EUROPEAN ECONOMIC COMMUNITY (EEC) - Alfiyah, Nur Inna; Andrianingsih, Very (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2021)
Globalization is a phenomenon that cannot be separated from human life, where all international structures and orders change. Easy access to information, technology and the exchange of goods, services and ideology make globalization a very important part. Changing the structure and economic, political and social order at this time requires existing countries to adapt to all changes brought about by globalization. The birth of non-state actors in globalization then brought about its own changes, especially in the economic field. This study aims to explain how the impact of the Greek economic crisis on the European economic community. The method used in this research is a qualitative method with a descriptive approach. The results of this study indicate that the economic interdependence between European countries which has led to the birth of the European Economic Community (EEC) is very influential on one another. This can be seen from how the Greek crisis was able to change the economic policy order of member countries of the European Economic Community (EEC).